Meningkatkan Daya Saing UMKM melalui Digital Marketing TikTok - Maulidiana, Ade Ega; Prajawati, Maretha Ika (Maliki Interdisciplinary Journal, 2025)
Strategic management plays a crucial role in enhancing the competitiveness and sustainability of micro-enterprises in the digital era. The implementation of appropriate functional strategies enables MSME actors to respond effectively to both internal and external challenges. One example can be seen in a culinary micro-enterprise in Malang Regency that has successfully utilized digital marketing through the TikTok platform to reach new consumers and build brand awareness effectively. Despite facing limitations in human resources and lacking a structured managerial system, the business has managed to maintain product quality and customer loyalty. Research findings indicate that the use of social media has proven to be an efficient promotional tool with a broad impact. Furthermore, the plan to develop products in the form of frozen food is seen as a strategic step to expand the market and increase added value. The integration of innovation, digital technology, and a commitment to quality has become the key to helping micro-enterprises move up the business ladder. This study emphasizes that the implementation of adaptive and market-oriented strategic management is essential for MSMEs to survive and grow amid increasingly competitive market conditions. This research adopts a descriptive qualitative approach, with data collected through direct interviews with micro-enterprise actors who served as the study subjects.